Синтез і властивості метал-вуглецевих нанокомпозитів Ni/C, Co/C ТА Cu/C з підвищенним вмістом металу - Bogatyrov, V. M.; Borysenko, M. V.; Oranska, O. I.; Galaburda, M. V.; Makhno, S. M.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2017)
Cu/C, Ni/C and Co/C nanocomposites with average size of crystallites of 50, 18, and 20 nm, respectively, have been synthesized, using two-step method, which includes mechanochemical treatment of polyethylene glycol and acetates of copper, nickel and cobalt, followed by pyrolysis of the mixture in an argon flow at 700 ° C. The carbon content in the composites was 5.2 - 17.2 wt.%. The specific surface area of the powders varies between 28-41 m2/g. The resistance to hydrothermal processing of nanocomposites was established and the electrophysical characteristics of nanopowders were investigated.